New Conotoxin SO-3 Targeting N-type Voltage-Sensitive Calcium Channels - Lei Wen; Sheng Yang; Wenxia Zhou; Peitang Huang; Yongxiang Zhang (Marine Drugs, 2006)
Selective blockers of the N-type voltage-sensitive calcium (CaV) channels are useful in the management of severe chronic pain. Here, the structure and function characteristics of a novel N-type CaV channel blocker, SO-3, are reviewed. SO-3 is a 25-amino acid conopeptide originally derived from the venom of Conus striatus, and contains the same 4-loop, 6-cysteine framework (C-C-CC-C-C) as O-superfamily conotoxins. The synthetic SO-3 has high analgesic activity similar to ÃÂ‰-conotoxin MVIIA (MVIIA), a selective N-type CaV channel blocker approved in the USA and Europe for the alleviation of persistent pain states. In electrophysiological studies, SO-3 shows more selectivity towards the N-type CaV channels than MVIIA. The dissimilarity between SO-3 and MVIIA in the primary and tertiary structures is further discussed in an attempt to illustrate the difference in selectivity of SO-3 and MVIIA towards N-type CaV channels.